2004
DOI: 10.1021/ol0491641
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Selectivity of Asymmetric Sulfur Ylide Epoxidation Reaction

Abstract: [structure: see text] We report the first theoretical studies on the asymmetric sulfonium ylide epoxidation reaction using a chiral sulfide that successfully reproduces the experimentally determined high enantiomeric excess. Calculations at the DFT level suggest that the transition states for the addition of the sulfonium ylide to benzaldehyde have energies which account for the observed enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Goodman and coworkers have recently reported a computational study 143 regarding the enantioselectivity in the epoxidation reaction catalyzed by the sulfides 35 , developed by Metzner and co-workers, 144 and 36 , by the Goodman group (Scheme 92). 145 …”
Section: Lewis/brønsted Base Catalysismentioning
confidence: 99%
“…Goodman and coworkers have recently reported a computational study 143 regarding the enantioselectivity in the epoxidation reaction catalyzed by the sulfides 35 , developed by Metzner and co-workers, 144 and 36 , by the Goodman group (Scheme 92). 145 …”
Section: Lewis/brønsted Base Catalysismentioning
confidence: 99%
“…Metzner postulates that this methyl group also controls the conformation of the ylide, as a steric clash in 27b renders 27a more favorable [16]. However, computational studies by Goodman revealed that 27a was not particularly favored over 27b, but it was substantially more reactive, thus providing the high enantioselectivity observed [17].…”
Section: Discussion Of Factors Affecting Diastereo-and Enantioselectimentioning
confidence: 99%
“…and good yields were obtained (Table 1. 17). High enantioselectivities were obtained in all cases, but diastereoselectivities were dependent both on the nitrogen activating group and on the imine substituent, with carbamate groups giving better diastereoselectivities than the corresponding sulfonyl groups.…”
mentioning
confidence: 90%
“…[2] At the same time, asymmetric processes (including direct sulfide catalyzed asymmetric reactions and indirect sulfide catalyzed asymmetric reactions) which involved sulfur ylides for the cascade reactions is another research topic of importance [3,4,2d] . To the best of our knowledge, whether the direct sulfide‐catalyzed asymmetric reactions or indirect sulfide‐catalyzed asymmetric reactions, the asymmetric [2+1] annulations, such as aldehyde epoxidations [3a–g,4a−g] and aldimine aziridinations, [3i–j] have been well established. However, only a few types of indirect sulfide‐catalyzed asymmetric [4+1] annulations to construct five‐membered cyclic compounds have been successfully developed in the past years [2d–f,4i−p] .…”
Section: Methodsmentioning
confidence: 99%